The Borrachudos Granitic Suite: Paleo- to Mesoproterozoic A-type Magmatism in the Southeastern São Francisco Craton (SE Brazil) - IVO ANTONIO DUSSIN; MARIO LUIZ S.C. CHAVES; TANIA MARA DUSSIN; PHILLIPPE ROSSI; JACQUES CHARVET (Anais da Academia Brasileira de Ciências)
Abstract The Borrachudos Granitic Suite (BGS) comprises an acid magmatism that occurred in the west edge of Araçuaí orogen (Late Neoproterozoic), southeastern Brazil. Previous papers attributed the magma genesis to crustal thickening related to an older Paleoproterozoic, Transamazonian orogeny. However, geochronological data indicate that BGS is younger, dominated by about 1.7 Ga granitoids hosted in the archean basement. To investigate the nature of this magmatism, mineralogical, geochemical, Nd-Sr isotopic studies in the BGS and genetically related metarhyolites inside the fold belt were carried out. High SiO2, K, Fe, F, Nb, Y, Zr and REE contents characterize granitoids and metarhyolites. The suite has ENd(T) values of -10.10 and -6.17, with TDM of 2.6-3.0 Ga, and initial 87Sr/86Sr ratio of 0.7057, indicating features of alkaline and anorogenic (A-type) within plate granitic magmas, derived from a Proterozoic crustal source. Therefore, we argue that an orogenic model for this magmatism is not viable. We propose that BGS is associated to crustal melting induced by mantle diapirism or mantle derived magmas related to the Paleoproterozoic extensional tectonic that produced crustal rifting, westward, precursory to the Espinhaço Supergroup basin. Beryl- and topaz-rich pegmatites of NYF-type intruded the granites as well as nearby host gneisses during BGS evolution.